Identification, genome-wide sequencing and analysis of drug resistance genes in a novel Vibrio harveyi strain isolated from yellowfin seabream - Zhihong, Huang; Cuiyu, Liu; Min, Guo; Dikuang, Peng; Chuchu, Lai; Kecheng, Zhu; Xueming, Dan; Min, Yang; Xuezhu, Lee (Aquaculture, 2025)
Yellowfin seabream (Acanthopagrus latus) is a fast-growing, adaptable species crucial for fish farming in southern China. However, as aquaculture of this species expands, diseases caused by bacteria, particularly Vibrio harveyi, are causing substantial economic losses. In this study, we isolated and identified a Vibrio harveyi strain denoted VH-AQ-SCAU-GZ23 from the diseased fish. Clinical signs of VH-AQ-SCAU-GZ23 infection were slow swimming, loss of appetite, loss of scales, severe liver congestion, and swelling of the gill filaments. VH-AQ-SCAU-GZ23 also induced an inflammatory response in yellowfin snapper spleen, liver, and brain tissue. To examine its pathogenicity and antibiotic susceptibility, we analyzed the genome sequence of this strain with third-generation high-throughput technology. The VH-AQ-SCAU-GZ23 genome was found to comprise a circular chromosome and three plasmids. Virulence factor analysis indicated that VH-AQ-SCAU-GZ23 contains a TLH gene encoding a thermolysin that increases virulence. Additionally, several antibiotic resistance genes were identified, including those encoding β-lactams, tetracyclines, aminoglycosides, quinolones, macrolides, peptides, and other antibiotics. To assess the drug sensitivity of those antibiotic resistance genes, we cloned ten resistance genes and transfected them into Escherichia coli DH5α for drug susceptibility testing. These resistance genes enhanced the resistance of DH5α to streptomycin, ampicillin, and penicillin G, among other antibiotics. Our study provides crucial support and a theoretical basis for advancing understanding of Vibrio harveyi. The insights gained are expected to provide guidance for future endeavors aimed at preventing and managing marine bacterial infections. •Pathogenic strain VH-AQ-SCAU-GZ23 isolated from diseased yellowfin seabream.•Vibrio harveyi confirmed via analysis:morphological, biochemical, and genetic analysis.•Identification of unique genome:ring chromosome, three ring plasmids, presence of Type III secretion system (T3SS) and TLH gene.•Antibiotic resistance genes detected across various classes.